CLINICAL AND CONE-BEAM COMPUTED TOMOGRAPHY CHARACTERISTICS OF PATIENTS WITH MANDIBULAR FRACTURES AT NATIONAL HOSPITAL OF ODONTOLOGY AND MAXILLOFACIAL SURGERY, HANOI, 2024–2026 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical and cone-beam computed tomography (CBCT) characteristics of patients with mandibular fractures treated at the National Hospital of Odontology and Maxillofacial Surgery, Hanoi, from 2024 to 2026.Subjects and methods: A retrospective cross-sectional study was conducted on 251 patients with mandibular fractures who underwent surgical treatment at the Department of Maxillofacial Surgery, National Hospital of Odontology and Maxillofacial Surgery, Hanoi, between June 2024 and June 2026. Clinical findings and CBCT characteristics were collected from medical records and preoperative imaging data.          Results: The mean age of patients was 28.3 ± 13.5 years, and males accounted for 71.71% of cases. Traffic accidents were the leading cause of mandibular fractures (78.09%). The most common clinical manifestations were pain at the fracture site (94.82%), malocclusion (86.85%), and limited mouth opening (82.07%). On CBCT imaging, fractures of the symphysis region were the most frequent (59.76%), followed by condylar fractures (52.59%). Multiple fracture sites were observed in most patients. Common associated maxillofacial injuries included maxillary and zygomatic arch fractures.Conclusions: Mandibular fractures mainly occurred in young male patients and were predominantly caused by traffic accidents. CBCT played an important role in evaluating fracture characteristics and supporting treatment planning.
Keywords: mandibular fracture, cone-beam computed tomography, maxillofacial trauma, condylar fracture, symphysis fracture